Rare bird documentation form for Lesser Black-backed Gull at Saylorville Dam in 1998 - Schoenewe, Lee A.et al (1998)
Rare bird documentation form for a Lesser Black-backed Gull at Saylorville Dam in Polk County, IA on November 4, 1998. Epson - sheet feed